Urgensi Peraturan Daerah Bantuan Hukum bagi Masyarakat Miskin dan Kelompok Rentan di Daerah Istimewa Yogyakarta - Andrie Irawan; Muhammad Haris (Nuansa Akademik: Jurnal Pembangunan Masyarakat, 2022)
The enactment of Law Number 16 of 2011 concerning Legal Aid shows the commitment of state administrators in absolute terms, but the issue of legal aid is not only a matter for the central government but also for local governments with the specificity of the region so that access to justice and equality before the law for citizens is more fulfilled by mutual support between the central and regional governments, as well as a more comprehensive legal aid regulation is needed not only for the poor but also for vulnerable groups, especially in the Special Region of Yogyakarta with the aim of there is an expansion of access to legal aid recipients and course better and more targeted legal aid services.